An evaluation of Iken fishing strategy in tropical Lekki lagoon, Nigeria - B. E. Emmanuel; L. O. Chukwu; B. B. Solarin (Advances in Aquaculture and Fisheries Management, 2023)
This paper presents the results of the investigations of the fish aggregating device which served as fisheries enhancement techniques for the improvement of the productivity of the Lekki Lagoon between March 2006 and February 2008. The performance of the floating Island (Iken fishery) depends on the size and the thickness. Chrysichythys nigrodigitatus contributed 25.51, 23.42 and 25.19% of the total weight of fish from floating Island with water hyacinth, Vossia sp and Cyperus sp dominant plant respectively. Tilapia guineensis contributed 17.0, 21.55 and 23.18% for water hyacinth, Vossia sp and Cyperus sp as dominant plant respectively. The fishing with acoustic yielded the highest catch by weight (47.22%) followed by fishing without acoustics (33.33%) with the least recorded in the open lagoon (19.44%). Management measures to maintain optimal production from Iken fishery should include the use of luxuriant water hyacinth which will reduce deforestation and erosion of the mangrove belt. The community managed resource enhancement should evolve from the existing traditional practices to meet both economic and social objectives as a major management strategy